PREVALENCE OF HEPATITIS B AND C VIRAL INFECTIONS IN PREGNANT WOMEN ATTENDING ANTENATAL CLINIC IN NNEWI, NIGERIA - Oluboyo, B.O; Ugochukwu, V.I; Oluboyo, A.O; Ihim, A.C; Chukwuma, G.O; Ogenyi, S.I; Onyemelukwe, A (European Scientific Journal, ESJ, 2014)
Infections due to Hepatitis B and C viruses are significant health problems around the globe, Nigeria inclusive. This study was conducted among 100 pregnant women attending ante natal clinic at NnamdiAzikiwe University Teaching Hospital, Nnewi, Anambra State, Nigeria to determine the seroprevalence of Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) and to determine whether liver amino transferases can be affected. The blood samples were tested for hepatitis B surface antigen (HBsAg) and Anti-HCV using HBsAg and Anti-HCV one step rapid test strip and furthermore using ELISA technique. Serum alanine aminotransferase (ALT) and serum aspartate aminotransferase (AST) activities were also estimated in all the subjects using Reitman - Frankel method. The results showed that six percent(6%) and one percent (1%) of the 100 blood samples tested positive for HBV and HCV respectively. The mean AST levels for HBsAg negative and positive subjects were 10.55±2.36 and 12.17±2.23 respectively while the mean ALT levels were 5.54±1.94and 8.00±3.10 respectively. The mean AST for anti-HCV negative and positive subjects were 10.67±2.38 and 9.00±0.00 respectively while the ALT were 5.71±2.09 and 4.00±0.00 respectively There was significant increase in the levels of ALT between the HBsAg positive and negative pregnant subjects (P<0.05). HBV and HCV infection can be present in pregnant women and can alter liver amino transferases. Therefore testing for HBsAg and Anti-HCV is recommended for all pregnant women at first prenatal and postnatal visit so that HBsAg and HCV positive mothers will receive prompt intervention.